Robin Hood : men in tights [videorecording (DVD)] - Brooks, Mel, 1926-; Brooks, Mel, 1926-; Elwes, Cary, 1962-; Yasbeck, Amy, 1962-; Rees, Roger, 1944-2015; Blankfield, Mark, 1950-; Chappelle, Dave; Hayes, Isaac; Ullman, Tracey; Stewart, Patrick, 1940-; DeLuise, Dom; Van Patten, Dick (Twentieth Century Fox Home Entertainment, 2006)
Robin Hood attempts to save England from Prince John and the Sheriff of Rottingham, while also winning the heart of Maid Marian.